2012
DOI: 10.1111/j.1399-0012.2012.01604.x
|View full text |Cite
|
Sign up to set email alerts
|

Defibrotide for the prevention of hepatic veno‐occlusive disease after hematopoietic stem cell transplantation: a systematic review

Abstract: Prophylactic use of defibrotide (DF) to prevent veno‐occlusive disease (VOD), a relatively common and high‐risk complication of hematopoietic stem cell transplantation (HSCT), may be an encouraging modality to reduce morbidity and mortality from VOD. However, conclusions remain unclear. We carried out a systematic review to summarize the state of knowledge. One randomized controlled trial (RCT), four cohort studies and eight case series studies were found, including a total of 1230 patients. The overall mean i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…The use of prophylactic ursodeoxycholic acid has been shown to reduce the incidence of SOS [ 171 ]. Defi brotide has shown some promise in decreasing the incidence of SOS, but large randomized controlled trials are lacking [ 242 ]. No clear evidence of preventive benefi t has been shown with prostaglandin E1, tissue plasminogen activator, N -acetylcysteine, human antithrombin III concentrate, activated protein C, low-dose heparin, albumin, or prednisone [ 216 , 241 , 243 , 244 ].…”
Section: Treatmentmentioning
confidence: 99%
“…The use of prophylactic ursodeoxycholic acid has been shown to reduce the incidence of SOS [ 171 ]. Defi brotide has shown some promise in decreasing the incidence of SOS, but large randomized controlled trials are lacking [ 242 ]. No clear evidence of preventive benefi t has been shown with prostaglandin E1, tissue plasminogen activator, N -acetylcysteine, human antithrombin III concentrate, activated protein C, low-dose heparin, albumin, or prednisone [ 216 , 241 , 243 , 244 ].…”
Section: Treatmentmentioning
confidence: 99%
“…22,23 Defibrotide has multiple and complex mechanisms of action, including anti-inflammatory, antiatherosclerotic, anti-ischemic, and antithrombotic properties. 1,4,7 Studies with defibrotide have also demonstrated increased plasmin activity, promotion of fibrinolysis via upregulation of tissue plasminogen activator and inhibition of tissue factor pathway, reduced circulating levels of plasminogen activator inhibitor-1, and increased concentration of endogenous prostaglandins (I 2 and E 2 ), which modulate thrombomodulin, platelets, and fibrinolysis. 1,7,22,24 Defibrotide may also be involved in the modulation of endothelial and leukocyte cellular interactions, which play a significant role in ischemic and reperfusion events due to alteration of endothelial cell membrane permeability, lipid peroxidation, free radical production, and recruitment of leukocyte adhesion to endothelial cells, resulting in vascular infiltration and subsequent endothelial damage.…”
Section: Clinical Pharmacologymentioning
confidence: 99%
“…VOD is implicated as one of the leading causes of HSCTrelated morbidity and mortality. 4 Typically, mild to moderate cases of VOD are self-limiting and resolve with minimal treatment; however, severe cases are associated with liver failure, hepatorenal syndrome, and multiorgan failure, with a mortality rate as high as 84%. 2,3,6,8 Defibrotide is the only approved drug for the treatment of VOD with renal or pulmonary dysfunction following HSCT; however, patients may also be helped by supportive care, including diuresis, transfusion, renal replacement therapy, and analgesia.…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the demonstration of the efficacy of defibrotide in the treatment of VOD, several studies investigated the role of this agent in prophylaxis [14][15][16][17][18][19]. In the review by Zhang L et al it was mentioned that most studies regarding prophylaxis involved pediatric patients and only one of them was a randomized controlled trial [20]. To the best of our knowledge, only few studies have investigated the role of defibrotide for prophylaxis in adult patients following allogeneic hematopoietic stem cell transplantation (AHSCT) [18,19].…”
Section: Introductionmentioning
confidence: 99%